AB0498 A True to Life Study on Effects of Switching from Oral to Subcutaneous Methotrexate. (9th June 2015) - Dolan, L.; Joshi, A.
Abstract : Background: Subcutaneous methotrexate has been shown to be more efficacious than oral methotrexate in the treatment of rheumatoid arthritis. However, there has been no reported difference in tolerability 1 . Objectives: Our study aimed to determine whether subcutaneous methotrexate had a better side effect profile and what effect it had upon disease control. Methods: We performed a retrospective observational study in our district general hospital. Thirty two patients with rheumatoid arthritis (21 seropositive and 11 seronegative) had switched from oral to subcutaneous Methotrexate between January 2013 and June 2014. Results: Of the 32 patients, 11 switched from oral to subcutaneous methotrexate due to intolerable side effects (mainly nausea, diarrhoea and mouth ulcers). Of these 11 patients, 7 patients (63.6%) had complete resolution of side effects but 4 patients (36.4%) suffered persistent nausea requiring a change in treatment. Disease control was assessed by DAS28-CRP recorded before and during treatment with subcutaneous methotrexate. Prior to commencing subcutaneous methotrexate the average DAS28-CRP was 4.60 and following treatment commencement this reduced to an average of 4.13. According to EULAR criteria 5 patients (20.8%) obtained a "good response" and 8 (33.3%) a "moderate response" to therapy. Eleven patients were classified as having "no response" to subcutaneous methotrexate and treatment was escalated to biologics in 8 patients. Two out of three patients classified as "no response" met either disease remission criteria or low disease activity criteria as per DAS28-CRP. At present 16 patients (50%) are still maintained on subcutaneous methotrexate and other disease modifying drugs without biologic agents, the mean DAS28-CRP for these patients is 3.29 indicating low disease activity. Conclusions: In summary, this study has shown that switching from oral to subcutaneous methotrexate can improve disease control and reduce incidence of side effects making medication more tolerable for patients. As a result of this study we propose that an early switch to subcutaneous methotrexate be considered for all patients with suboptimal disease control or intolerable side effects. References: Braun et al. Comparison of the clinical efficacy and safety of subcutaneous versus oral administration of methotrexate in patients with active rheumatoid arthritis: results of a six-month, multicentre, randomized, double-blind, controlled, phase IV trial. Arthritis Rheumatology 2008; 58(1):73-81. Disclosure of Interest: None declared